Derivation of a Micro-Macro Link for Collective Decision-Making Systems: Uncover Network Features Based on Drift Measurements - Khaluf, Yara; Dorigo, Marco; Hamann, Heiko; Valentini, Gabriele; Bartz-Beielstein, T. (13th International Conference on Parallel Problem Solving from Nature (PPSN 2014))

Evolution of Collective Behaviors by Minimizing Surprise - Hamann, Heiko; Sayama, Hiroki; Rieffel, John; Risi, Sebastian; Doursat, Rene; Lipson, Hod (14th Int. Conf. on the Synthesis and Simulation of Living Systems (ALIFE 2014))

A Swarm Robotics Approach to Task Allocation Under Soft Deadlines and Negligible Switching Costs - Cervera, Enric; Khaluf, Yara; Birattari, Mauro; Hamann, Heiko; Pobil, Angel P. del; Chinellato, Eris; Martinez-Martin, Ester; Hallam, John; Morales, Antonio (Simulation of Adaptive Behavior (SAB 2014))

A Review Corpus for Argumentation Analysis - Wachsmuth, Henning; Trenkmann, Martin; Stein, Benno; Engels, Gregor; Palakarska, Tsvetomira (Proceedings of the 15th International Conference on Intelligent Text Processing and Computational Linguistics)

Untersuchung des Erreichbarkeitsproblems in ungerichteten Graphen bezüglich den Komplexitätsklassen L und SL - Biermeier, Felix

Evaluierung von Initialisierungsmethoden für Fuzzy-k-means Algorithmen - Sauer, Malte

Rainbow connection number of graph power and graph products - Basavaraju, Manu; Chandran, L Sunil; Rajendraprasad, Deepak; Ramaswamy, Arunselvan (Graphs and Combinatorics)

Rainbow connection number and radius - Basavaraju, Manu; Chandran, L Sunil; Rajendraprasad, Deepak; Ramaswamy, Arunselvan (Graphs and Combinatorics)

Twenty years of learning with the World Wide Web - Keil, Reinhard; Selke, Harald; Winkelnkemper, Felix
n the summer of 1994, courses at universities were supported for the first time through the use of the World Wide Web. With the introduction of this new technology, high expectations quickly arose that the established forms of teaching and learning in schools and universities would be replaced and that the institutions themselves might even prove to be superfluous. Twenty years later, it turns out that there is a great gap between hope and reality. Some of the ideas at the time that, for example, having access to the world's knowledge at any time would make textbooks superfluous, turned out to be naive in retrospect. Characteristic of the ideas at that time was the assumption that didactic and organizational problems of teaching and learning could be solved purely technically.

Zwischen Design und Flexibilität - Zur Ergonomie des Flat Design - Winkelnkemper, Felix; Keil, Reinhard

Forschendes Lernen durch semantisches Positionieren - Jakoblew , Marcel; Keil, Reinhard; Winkelnkemper, Felix (Proceedings der HDI 2014)

Hypothesengeleitete Gestaltung von Benutzungsoberflächen - Keil, Reinhard; Schild, Christian

Knowledge integration processes and distributed knowledge organization - Keil, Reinhard

MaxiNet: Distributed Emulation of Software-Defined Networks - Wette, Philip; Dräxler, Martin; Schwabe, Arne; Wallaschek, Felix; Zahraee, Mohammad Hassan; Karl, Holger (Proceedings of the 2014 IFIP Networking Conference (Networking 2014))
Network emulations are widely used for testing novel network protocols and routing algorithms in realistic scenarios. Up to now, there is no emulation tool that is able to emulate large software-deﬁned data center networks that consist of several thousand nodes. Mininet is the most common tool to emulate Software-Deﬁned Networks of several hundred nodes. We extend Mininet to span an emulated network over several physical machines, making it possible to emulate networks of several thousand nodes on just a handful of physical machines. This enables us to emulate, e.g., large data center networks. To test this approach, we additionally introduce a trafﬁc generator for data center trafﬁc. Since there are no data center trafﬁc traces publicly available we use the results of two recent trafﬁc studies to create synthetic trafﬁc. We show the design and discuss some challenges we had in building our trafﬁc generator. As a showcase for our work we emulated a data center consisting of 3200 hosts on a cluster of only 12 physical machines. We show the resulting workloads and the trade-offs involved.

Verified Service Compositions by Template-Based Construction - Walther, Sven; Wehrheim, Heike (Proceedings of the 11th International Symposium on Formal Aspects of Component Software (FACS))
Today, service compositions often need to be assembled or changed on-the-fly, which leaves only little time for quality assurance. Moreover, quality assurance is complicated by service providers only giving information on their services in terms of domain specific concepts with only limited semantic meaning. In this paper, we propose a method to construct service compositions based on pre-verifiedtemplates. Templates, given as workflow descriptions, are typed over a (domain-independent) template ontology defining concepts and predicates. Templates are proven correct using an abstract semantics, leaving the specific meaning of ontology concepts open, however, only up to given ontology rules. Construction of service compositions amounts to instantiation of templates with domain-specific services.Correctness of an instantiation can then simply be checked by verifying that the domain ontology(a) adheres to the rules of the template ontology, and (b) fulfills the constraints of the employed template.

Using Application Layer Knowledge in Routing and Wavelength Assignment Algorithms - Wette, Philip; Karl, Holger (Proceedings of the IEEE International Conference on Communications 2014)
Preemptive Routing and Wavelength Assignment (RWA) algorithms preempt established lightpaths in case notenough resources are available to set up a new lightpath in aWavelength Division Multiplexing (WDM) network. The selectionof lightpaths to be preempted relies on internal decisions of theRWA algorithm. Thus, if dedicated properties of the networktopology are required by the applications running on the network,these requirements have to be known to the RWA algorithm.We present a family of preemptive RWA algorithms for WDMnetworks. These algorithms have two distinguishing features: a)they can handle dynamic traffic by on-the-fly reconfiguration,and b) users can give feedback for reconfiguration decisions andthus influence the preemption decision of the RWA algorithm,leading to networks which adapt directly to application needs.This is different from traffic engineering where the network is(slowly) adapted to observed traffic patterns.Our algorithms handle various WDM network configurationsincluding networks consisting of heterogeneous WDM hardware.To this end, we are using the layered graph approach togetherwith a newly developed graph model that is used to determineconflicting lightpaths.

Untersuchung transitiver Eigenschaften der Technik "Programs from Proofs" - Korth, Philipp

Tragedy of the Common Cloud - Game Theory on the Infrastructure-as-a-Service Market - Künsemöller, Jörn

Towards Systematic Configuration for Architecture Validation - Becker, Matthias; Becker, Steffen; Besova, Galina; Walther, Sven; Wehrheim, Heike (Proceedings of the 40th Euromicro Conference on Software Engineering and Advanced Applications (Work in Progress Session))

Towards a Flexible and Privacy-Preserving Reputation System for Markets of Composed Services - Brangewitz, Sonja; Jungmann, Alexander; Petrlic, Ronald; Platenius, Marie Christin (Proceedings of the 6th International Conferences on Advanced Service Computing (SERVICE COMPUTATION))
One future goal of service-oriented computing is to realize global markets of composed services. On such markets, service providers offer services that can be flexibly combined with each other. However, most often, market participants are not able to individually estimate the quality of traded services in advance. As a consequence, even potentially profitable transactions between customers and providers might not take place. In the worst case, this can induce a market failure. To overcome this problem, we propose the incorporation of reputation information as an indicator for expected service quality. We address On-The-Fly Computing as a representative environment of markets of composed services. In this environment, customers provide feedback on transactions. We present a conceptual design of a reputation system which collects and processes user feedback, and provides it to participants in the market. Our contribution includes the identification of requirements for such a reputation system from a technical and an economic perspective. Based on these requirements, we propose a flexible solution that facilitates the incorporation of reputation information into markets of composed services while simultaneously preserving privacy of customers who provide feedback. The requirements we formulate in this paper have just been partially met in literature. An integrated approach, however, has not been addressed yet.

Thread Shadowing: Using Dynamic Redundancy on Hybrid Multi-cores for Error Detection - Meisner, Sebastian; Platzner, Marco (Proceedings of the 10th International Symposium on Applied Reconfigurable Computing (ARC))
Dynamic thread duplication is a known redundancy technique for multi-cores. The approach duplicates a thread under observation for some time period and compares the signatures of the two threads to detect errors. Hybrid multi-cores, typically implemented on platform FPGAs, enable the unique option of running the thread under observation and its copy in different modalities, i.e., software and hardware. We denote our dynamic redundancy technique on hybrid multi-cores as thread shadowing. In this paper we present the concept of thread shadowing and an implementation on a multi-threaded hybrid multi-core architecture. We report on experiments with a block-processing application and demonstrate the overheads, detection latencies and coverage for a range of thread shadowing modes. The results show that trans-modal thread shadowing, although bearing long detection latencies, offers attractive coverage at a low overhead.

Template-based Generation of Semantic Services - Mohr, Felix; Walther, Sven (Proceedings of the 14th International Conference on Software Reuse (ICSR))
There are many technologies for the automation of processesthat deal with services; examples are service discovery and composition.Automation of these processes requires that the services are described semantically. However, semantically described services are currently not oronly rarely available, which limits the applicability of discovery and composition approaches. The systematic support for creating new semanticservices usable by automated technologies is an open problem.We tackle this problem with a template based approach: Domain independent templates are instantiated with domain specific services andboolean expressions. The obtained services have semantic descriptionswhose correctness directly follows from the correctness of the template.Besides the theory, we present experimental results for a service repository in which 85% of the services were generated automatically.

Template Embedding: Using Application Architecture to Allocate Resources in Distributed Clouds - Keller, Matthias; Robbert, Christoph; Karl, Holger (Proceedings of 7th International Conference on Utility and Cloud Computing (UCC))
In distributed cloud computing, application deployment across multiple sites can improve quality of service. Recent research developed algorithms to find optimal locations for virtual machines. However, those algorithms assume to have either single-tier applications or a fixed number of virtual machines – a strong simplification of reality. This paper investigates the placement and scaling of complex application architectures. An application is dynamically scaled to fit both the current demand situation and the currently available infrastructure resources. We compare two approaches: The first one is based on virtual network embedding. The second approach is a novel method called Template Embedding. It is based on a hierarchical 1-allocation hub flow problem and combines applica- tion scaling and embedding in one step. Extensive experiments on 43200 network configurations showed that Template Embedding outperforms virtual network embedding in all cases in three metrics: success rate, solution quality, and runtime. This positive result shows that template embedding is a promising approach for distributed cloud resource allocation.

Tampering attacks in pairing-based cryptography - Blömer, Johannes; Günther, Peter; Liske, Gennadij (Proceedings of Fault Tolerance and Diagnosis in Cryptography(FDTC))
In the last decade pairings have become an important, and often indispensable, ingredient in the construction of identity-based and attribute-based cryptosystems, as well as group signatures and credential systems. Consequently, the applicability of timing, power, or fault attacks to implementations of pairings is an important research topic. We will review some of the known results in this area.

Specifying and Placing Chains of Virtual Network Functions - Dräxler, Sevil; Keller, Matthias; Karl, Holger (Proceedings of the 3rd International Conference on Cloud Networking (CloudNet))
Network appliances perform different functions on network flows and constitute an important part of an operator’s network. Normally, a set of chained network functions process network flows. Following the trend of virtualization of networks, virtualization of the network functions has also become a topic of interest. We define a model for formalizing the chaining of network functions using a context-free language. We process deployment requests and construct virtual network function graphs that can be mapped to the network. We describe the mapping as a Mixed Integer Quadratically Constrained Program (MIQCP) for finding the placement of the network functions and chaining them together considering the limited network resources and requirements of the functions. We have performed a Pareto set analysis to investigate the possible trade-offs between different optimization objectives.

Simulating load-dependent operation of picocells - Roeske, Daniel

SeSAME: Modeling and Analyzing High-Quality Service Compositions - Arifulina, Svetlana; Becker, Matthias; Platenius, Marie Christin; Walther, Sven (Proceedings of the 29th IEEE/ACM International Conference on Automated Software Engineering (ASE 2014))
Today, software components are traded on markets in form of services. These services can also be service compositions consisting of several services. If a software architect wants to provide such a service composition in the market for trade, she needs to perform several tasks: she needs to model the composition, to discover existing services to be part of that composition, and to analyze the composition's functional correctness as well as its quality, e.g., performance. Up to now, the architect needed to find and use different tools for these tasks. Typically, these tools are not interoperable with each other. We provide the tool SeSAME that supports a software architect in all of these tasks. SeSAME is an integrated Eclipse-based tool-suite providing a comprehensive service specification language to model service compositions and existing services. Furthermore, it includes modules for service matching, functional analysis, and non-functional analysis. SeSAME is the first tool that integrates all these tasks into one tool-suite and, thereby, provides holistic support for trading software services. Thus, it contributes to a software provider's market success.

Security and Privacy Challenges in On-The-Fly Computing - Petrlic, Ronald; Jungmann, Alexander; Platenius, Marie Christin; Schäfer, Wilhelm; Sorge, Christoph (Tagungsband der 4. Konferenz Software-Technologien und -Prozesse (STeP 2014))
On-The-Fly (OTF) Computing constitutes an approach towards highly dynamic and individualized software markets. Based on service-oriented computing, OTF Computing is about realizing global markets of services that can be flexibly combined. We report on our current research activities, the security and privacy implications thereof, and our approaches to tackle the challenges. Furthermore, we discuss how the security and privacy challenges are addressed in research projects similar to OTF Computing.

Secure Distributed Data Structures for Peer-to-Peer-based Social Networks - Janiuk, Jens; Mäcker, Alexander; Graffi, Kalman (Proceedings of the International Conference on Collaboration Technologies and Systems (CTS))
Online social networks are attracting billions of nowadays, both on a global scale as well as in social enterprise networks. Using distributed hash tables and peer-to-peer technology allows online social networks to be operated securely and efficiently only by using the resources of the user devices, thus alleviating censorship or data misuse by a single network operator. In this paper, we address the challenges that arise in implementing reliably and conveniently to use distributed data structures, such as lists or sets, in such a distributed hash-tablebased online social network. We present a secure, distributed list data structure that manages the list entries in several buckets in the distributed hash table. The list entries are authenticated, integrity is maintained and access control for single users and also groups is integrated. The approach for secure distributed lists is also applied for prefix trees and sets, and implemented and evaluated in a peer-to-peer framework for social networks. Evaluation shows that the distributed data structure is convenient and efficient to use and that the requirements on security hold.

Scheduling Shared Continuous Resources on Many-Cores - Brinkmann, Andre; Kling, Peter; Meyer auf der Heide, Friedhelm; Nagel, Lars; Riechers, Sören; Suess, Tim (Proceedings of the 26th ACM Symposium on Parallelism in Algorithms and Architectures (SPAA))
We consider the problem of scheduling a number of jobs on $m$ identical processors sharing a continuously divisible resource. Each job j comes with a resource requirement r_j \in {0,1}. The job can be processed at full speed if granted its full resource requirement. If receiving only an x-portion of r_j, it is processed at an x-fraction of the full speed. Our goal is to find a resource assignment that minimizes the makespan (i.e., the latest completion time). Variants of such problems, relating the resource assignment of jobs to their processing speeds, have been studied under the term discrete-continuous scheduling. Known results are either very pessimistic or heuristic in nature.In this paper, we suggest and analyze a slightly simplified model. It focuses on the assignment of shared continuous resources to the processors. The job assignment to processors and the ordering of the jobs have already been fixed. It is shown that, even for unit size jobs, finding an optimal solution is NP-hard if the number of processors is part of the input. Positive results for unit size jobs include an efficient optimal algorithm for 2 processors. Moreover, we prove that balanced schedules yield a 2-1/m-approximation for a fixed number of processors. Such schedules are computed by our GreedyBalance algorithm, for which the bound is tight.

RSA-Full Domain Hash Revisited - Rath, Timo
RSA Full Domain Hash ist im Zufallsorakelmodell ein EUF-CMA sicheres Signaturverfahren (existentially unforgeable under chosen-message attacks). Der Sicherheitsbeweis wird unter anderem in der Vorlesung Einführung in die Kryptographie vorgestellt. Auch bei einer genaueren Analyse verliert man bei der Reduktion einen Faktor \nicefrac{1}{q_{s}}(wobei q_{s}die Anzahl der Anfragen an das Signaturorakel darstellt), was für die Praxis in relativ großen Systemparametern (RSA-Modul) resultiert [1].Seit der Veröffentlichung von [2] wurde geglaubt, dass der Faktor \nicefrac{1}{q_{s}}optimal ist. Erst zehn Jahre später offenbarten die Autoren von [3] einen Fehler in [2] und zeigten eine bessere Reduktion allerdings unter einer etwas stärkeren Sicherheitsannahme.Die Ergebnisse aus [3] lassen sich auf PSS-Verfahren (Probabilistic Signature Scheme), das z.B. in PKCS #1 benutzt wird, übertragen und sind somit von großer Bedeutung für die Praxis. Weiterhin sind die in den Beweisen verwendete Techniken nützlich auch bei anderen kryptographischen Verfahren.In Rahmen dieser Arbeit sollen die entsprechenden Sicherheitsbeweise aufgearbeitet und dessen Auswirkungen für die Praxis analysiert werden.[1] J.S. Coron, “On the Exact Security of Full Domain Hash”, CRYPTO 2000. LNCS 1880, pp. 229-235, 2000.[2] J.S. Coron, “Optimal security proofs for PPS and other signature schemes”, EUROCRYPT 2002. LNCS 2332, pp 272-287, 2002.[3] S.A. Kakvi and E. Kiltz, “Optimal Security Proofs for Full Domain Hash, Revisited”, in EUROCRYPT 2012. LNCS 7237, pp 537-553, 2012.

Routing Games with Progressive Filling - Harks, Tobias; Höfer, Martin; Schewior, Kevin; Skopalik, Alexander (Proceedings of the 33rd Annual IEEE International Conference on Computer Communications (INFOCOM'14))
Max-min fairness (MMF) is a widely known approach to a fair allocation of bandwidth to each of the users in a network. This allocation can be computed by uniformly raising the bandwidths of all users without violating capacity constraints. We consider an extension of these allocations by raising the bandwidth with arbitrary and not necessarily uniform time-depending velocities (allocation rates). These allocations are used in a game-theoretic context for routing choices, which we formalize in progressive filling games (PFGs).We present a variety of results for equilibria in PFGs. We show that these games possess pure Nash and strong equilibria. While computation in general is NP-hard, there are polynomial-time algorithms for prominent classes of Max-Min-Fair Games (MMFG), including the case when all users have the same source-destination pair. We characterize prices of anarchy and stability for pure Nash and strong equilibria in PFGs and MMFGs when players have different or the same source-destination pairs. In addition, we show that when a designer can adjust allocation rates, it is possible to design games with optimal strong equilibria. Some initial results on polynomial-time algorithms in this direction are also derived.

RoBuSt: A Crash-Failure-Resistant Distributed Storage System - Scheideler, Christian; Setzer, Alexander; Eikel, Martina (Proceedings of the 18th International Conference on Principles of Distributed Systems (OPODIS))
In this work we present the first distributed storage system that is provably robust against crash failures issued by an adaptive adversary, i.e., for each batch of requests the adversary can decide based on the entire system state which servers will be unavailable for that batch of requests. Despite up to \gamma n^{1/\log\log n} crashed servers, with \gamma>0 constant and n denoting the number of servers, our system can correctly process any batch of lookup and write requests (with at most a polylogarithmic number of requests issued at each non-crashed server) in at most a polylogarithmic number of communication rounds, with at most polylogarithmic time and work at each server and only a logarithmic storage overhead. Our system is based on previous work by Eikel and Scheideler (SPAA 2013), who presented IRIS, a distributed information system that is provably robust against the same kind of crash failures. However, IRIS is only able to serve lookup requests. Handling both lookup and write requests has turned out to require major changes in the design of IRIS.

Response Time-Optimized Distributed Cloud Resource Allocation - Keller, Matthias; Karl, Holger (Proceedings of the SIGCOMM workshop on Distributed cloud computing)
In the near future many more compute resources will be available at different geographical locations. To minimize the response time of requests, application servers closer to the user can hence be used to shorten network round trip times. However, this advantage is neutralized if the used data centre is highly loaded as the processing time of re- quests is important as well. We model the request response time as the network round trip time plus the processing time at a data centre.We present a capacitated facility location problem formal- ization where the processing time is modelled as the sojourn time of a queueing model. We discuss the Pareto trade-off between the number of used data centres and the resulting response time. For example, using fewer data centres could cut expenses but results in high utilization, high response time, and smaller revenues.Previous work presented a non-linear cost function. We prove its convexity and exploit this property in two ways: First, we transform the convex model into a linear model while controlling the maximum approximation error. Sec- ond, we used a convex solver instead of a slower non-linear solver. Numerical results on network topologies exemplify our work.

Reputationssysteme für zusammengesetzte Dienstleistungen - Pahl, David

Reducing Energy Consumption of Radio Access Networks - Herlich, Matthias
Radio access networks (RANs) have become one of the largest energy consumers of communication technology [LLH+13] and their energy consumption is predicted to increase [FFMB11]. To reduce the energy consumption of RANs different techniques have been proposed. One of the most promising techniques is the use of a low-power sleep mode. However, a sleep mode can also reduce the performance. In this dissertation, I quantify how much energy can be conserved with a sleep mode and which negative effects it has on the performance of RANs. Additionally, I analyze how a sleep mode can be enabled more often and how the performance can be kept high. First, I quantify the effect of power-cycle durations on energy consumption and latency in an abstract queuing system. This results in a trade-off between energy consumption and latency for a single base station (BS). Second, I show that considering a network as a whole (instead of each BS individually) allows the energy consumption to be reduced even further. After these analyses, which are not specific for RANs, I study RANs for the rest of the dissertation. RANs need to both detect and execute the requests of users. Because detection and execution of requests have different requirements, I analyze them independently. I quantify how the number of active BSs can be reduced if the detection ranges of BSs are increased by cooperative transmissions. Next, I analyze how more BSs can be deactivated if the remaining active BSs cooperate to transmit data to the users. However, in addition to increasing the range, cooperative transmissions also radiate more power. This results in higher interference for other users which slows their transmissions down and, thus, increases energy consumption. Therefore, I describe how the radiated power of cooperative transmissions can be reduced if instantaneous channel knowledge is available. Because the implementation in real hardware is impractical for demonstration purposes, I show the results of a simulation that incorporates all effects I studied analytically earlier. In conclusion, I show that a sleep mode can reduce the energy consumption of RANs if applied correctly. To apply a sleep mode correctly, it is necessary to consider power-cycle durations, power profiles, and the interaction of BSs. When this knowledge is combined the energy consumption of RANs can be reduced with only a slight loss of performance. Because this results in a trade-off between energy consumption and performance, each RAN operator has to decide which trade-off is preferred.

Re-Chord: A Self-stabilizing Chord Overlay Network - Kniesburges, Sebastian; Koutsopoulos, Andreas; Scheideler, Christian (Theory of Computing Systems)
The Chord peer-to-peer system is considered, together with CAN, Tapestry and Pastry, as one of the pioneering works on peer-to-peer distributed hash tables (DHT) that inspired a large volume of papers and projects on DHTs as well as peer-to-peer systems in general. Chord, in particular, has been studied thoroughly, and many variants of Chord have been presented that optimize various criteria. Also, several implementations of Chord are available on various platforms. Though Chord is known to be very efficient and scalable and it can handle churn quite well, no protocol is known yet that guarantees that Chord is self-stabilizing, i.e., the Chord network can be recovered from any initial state in which the network is still weakly connected. This is not too surprising since it is known that the Chord network is not locally checkable for its current topology. We present a slight extension of the Chord network, called Re-Chord (reactive Chord), that turns out to be locally checkable, and we present a self-stabilizing distributed protocol for it that can recover the Re-Chord network from any initial state, in which the n peers are weakly connected, in O(nlogn) communication rounds. We also show that our protocol allows a new peer to join or an old peer to leave an already stable Re-Chord network so that within O(logn)^2) communication rounds the Re-Chord network is stable again.

Randomized Online Algorithms for Set Cover Leasing Problems - Abshoff, Sebastian; Markarian, Christine; Meyer auf der Heide, Friedhelm (Proceedings of the 8th Annual International Conference on Combinatorial Optimization and Applications (COCOA))
In the leasing variant of Set Cover presented by Anthony et al.[1], elements U arrive over time and must be covered by sets from a familyF of subsets of U. Each set can be leased for K different periods of time.Let |U| = n and |F| = m. Leasing a set S for a period k incurs a cost ckS and allows S to cover its elements for the next lk time steps. The objectiveis to minimize the total cost of the sets leased, such that elements arrivingat any time t are covered by sets which contain them and are leased duringtime t. Anthony et al. [1] gave an optimal O(log n)-approximation forthe problem in the offline setting, unless P = NP [22]. In this paper, wegive randomized algorithms for variants of Set Cover Leasing in the onlinesetting, including a generalization of Online Set Cover with Repetitionspresented by Alon et al. [2], where elements appear multiple times andmust be covered by a different set at each arrival. Our results improve theO(log2(mn)) competitive factor of Online Set Cover with Repetitions [2]to O(log d log(dn)) = O(logmlog(mn)), where d is the maximum numberof sets an element belongs to.

Quality of Service in Network Creation Games - Cord-Landwehr, Andreas; Mäcker, Alexander; Meyer auf der Heide, Friedhelm (Proceedings of the 10th International Conference on Web and Internet Economics (WINE))
Network creation games model the creation and usage costs of networks formed by n selfish nodes. Each node v can buy a set of edges, each for a fixed price α > 0. Its goal is to minimize its private costs, i.e., the sum (SUM-game, Fabrikant et al., PODC 2003) or maximum (MAX-game, Demaine et al., PODC 2007) of distances from v to all other nodes plus the prices of the bought edges. The above papers show the existence of Nash equilibria as well as upper and lower bounds for the prices of anarchy and stability. In several subsequent papers, these bounds were improved for a wide range of prices α. In this paper, we extend these models by incorporating quality-of-service aspects: Each edge cannot only be bought at a fixed quality (edge length one) for a fixed price α. Instead, we assume that quality levels (i.e., edge lengths) are varying in a fixed interval [βˇ,β^] , 0 series = LNCS

PBlaman: performance blame analysis based on Palladio contracts - Brüseke, Frank; Wachsmuth, Henning; Engels, Gregor; Becker, Steffen (Proceedings of the 4th International Symposium on Autonomous Minirobots for Research and Edutainment)

Provider Competition in Infrastructure-as-a-Service - Künsemöller, Jörn; Brangewitz, Sonja; Karl, Holger; Haake, Claus-Jochen (Proceedings of the 2014 IEEE International Conference on Services Computing (SCC))
This paper explores how cloud provider competition inﬂuences instance pricing in an IaaS (Infrastructure-as-a-Service) market. When reserved instance pricing includes an on-demand price component in addition to a reservation fee (two-part tariffs), different providers might offer different price combinations, where the client’s choice depends on its load proﬁle. We investigate a duopoly of providers and analyze stable market prices in two-part tariffs. Further, we study offers that allow a speciﬁed amount of included usage (three-part tariffs). Neither two-part nor three-part tariffs produce an equilibrium market outcome other than a service pricing that equals production cost, i.e., complex price structures do not signiﬁcantly affect the results from ordinary Bertrand competition.

Programs from Proofs -- Approach and Applications - Wonisch, Daniel; Schremmer, Alexander; Wehrheim, Heike (Proceedings of the Software Engineering Conference (SE))
Proof-carrying code approaches aim at safe execution of untrusted code by having the code producer attach a safety proof to the code which the code consumer only has to validate. Depending on the type of safety property, proofs can however become quite large and their validation - though faster than their construction - still time consuming. In this paper we introduce a new concept for safe execution of untrusted code. It keeps the idea of putting the time consuming part of proving on the side of the code producer, however, attaches no proofs to code anymore but instead uses the proof to transform the program into an equivalent but more eﬃciently veriﬁable program. Code consumers thus still do proving themselves, however, on a computationally inexpensive level only. Experimental results show that the proof eﬀort can be reduced by several orders of magnitude, both with respect to time and space.

Principles of Robust Medium Access and an Application to Leader Election - Awerbuch, Baruch; Richa, Andrea W.; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (Transactions on Algorithms)
This article studies the design of medium access control (MAC) protocols for wireless networks that are provably robust against arbitrary and unpredictable disruptions (e.g., due to unintentional external interference from co-existing networks or due to jamming). We consider a wireless network consisting of a set of n honest and reliable nodes within transmission (and interference) range of each other, and we model the external disruptions with a powerful adaptive adversary. This adversary may know the protocol and its entire history and can use this knowledge to jam the wireless channel at will at any time. It is allowed to jam a (1 − )-fraction of the timesteps, for an arbitrary constant > 0 unknown to the nodes. The nodes cannot distinguish between the adversarial jamming or a collision of two or more messages that are sent at the same time. We demonstrate, for the first time, that there is a local-control MAC protocol requiring only very limited knowledge about the adversary and the network that achieves a constant (asymptotically optimal) throughput for the nonjammed time periods under any of the aforementioned adversarial strategies. The derived principles are also useful to build robust applications on top of the MAC layer, and we present an exemplary study for leader election, one of the most fundamental tasks in distributed computing.

Modeling Review Argumentation for Robust Sentiment Analysis - Wachsmuth, Henning; Trenkmann, Martin; Stein, Benno; Engels, Gregor (Proceedings of COLING 2014, the 25th International Conference on Computational Linguistics: Technical Papers)

Oblique incidence of semi-guided waves on rectangular slab waveguide discontinuities: A vectorial QUEP solver - Hammer, Manfred (Optics Communications)
The incidenceofthin-film-guided, in-planeunguidedwavesatobliqueanglesonstraightdiscontinuities of dielectricslabwaveguides,anearlyproblemofintegratedoptics,isbeingre-considered.The3-D frequencydomainMaxwellequationsreducetoaparametrizedinhomogeneousvectorialproblemona 2-D computationaldomain,withtransparent-influx boundaryconditions.Weproposearigorousvec- torial solverbasedonsimultaneousexpansionsintopolarizedlocalslabeigenmodesalongthetwo orthogonal crosssectioncoordinates(quadridirectionaleigenmodepropagationQUEP).Thequasi-ana- lytical schemeisapplicabletoconfigurations with — in principle — arbitrary crosssectiongeometries. Examples forahigh-contrastfacetofanasymmetricslabwaveguide,forthelateralexcitationofa channel waveguide,andforastepdiscontinuitybetweenslabwaveguidesofdifferentthicknessesare discussed.
Keywords: tet_topic_waveguide; tet_topic_numerics

On-the-Fly Computing: Automatic Service Discovery and Composition in Heterogeneous Domains - Huma, Zille; Gerth, Christian; Engels, Gregor (Computer Science - Research and Development)
In software markets of the future, customer-specific software will be developed on demand based on distributed software and hardware services. Based on a customer-specific request, available service offers have to be discovered and composed into sophisticated IT services that fulfill the customer's request.A prerequisite of this vision are rich service descriptions, which comprise structural as well as behavioral aspects of the services, otherwise an accurate service discovery and composition is not possible. However, automatic matching of service requests and offers specified in rich service descriptions for the purpose of service discovery is a complex task, due to the multifaceted heterogeneity of the service partners. This heterogeneity includes the use of different specification languages, different underlying ontologies, or different levels of granularity in the specification itself.In this article, we present a comprehensive approach for service discovery and composition, which overcomes the underlying heterogeneity of the service partners. Based on a realistic case study of our industrial partner from the e-tourism domain, we first introduce an automatic matching mechanism for service requests and offers specified in a rich service description language. In addition, we propose an automatic service composition approach, which determines possible service compositions by composing the service protocols through a composition strategy based on labeled transition systems.

iSoNTRE: The Social Network Transformer into Recommendation Engine - Abu Quba Rana, Chamsi; Hassas, Salima; Usama, Fayyad; Alshomary, Milad; Gertosio, Christine (2014 IEEE/ACS 11th International Conference on Computer Systems and Applications (AICCSA))

A Probabilistic Expectation Maximization Algorithm for Multivariate Laplacian Mixtures - Brauer, Sascha

Analysis of Agglomerative Clustering - Ackermann, Marcel Rudolf; Blömer, Johannes; Kuntze, Daniel; Sohler, Christian (Algorithmica)

A Theoretical and Experimental Comparison of the EM and SEM Algorithm - Blömer, Johannes; Bujna, Kathrin; Kuntze, Daniel (2014 22nd International Conference on Pattern Recognition)